University Students, Academic Structures and the Processes of Integration - Ige, B. O.; Naidoo, K. L. (South African Journal of Higher Education, 2022)
This special issue on Finding a Place to Belong: University Students, Academic Structures and the Processes of Integration contains nine papers on opportunities of belonging and highlights the cultivation of belonging as a fundamental for addressing inequality and inequity in a linguistically and culturally diverse higher education context. Here, belonging challenges the dominant university ideology, which can elude the marginalised or underserved student and staff groups of learning communities. The combination of individual/group agency and identity negotiation for developing and implementing enablers of belonging reveals the challenges and complexity of deconstructing belonging. The papers focus on the barriers and opportunities of belonging and the interaction of agency and enablers of belonging, such as equitable vision, policy, programmes and commitment, as a product of belonging.